Two new ‘Asura-like’ Cyana Walker, 1854 from Africa (Lepidoptera, Erebidae, Arctiinae) - Volynkin, Anton V. (Zootaxa, 2019)
Cyana Walker, 1854 is one of the most species-rich genera within the tribe Lithosiini Billberg of the subfamily Arctiinae Leach, family Erebidae Leach. The genus is widely distributed in tropics of Africa and Madagascar, south of the Arabian Peninsula, South and East Asia (including Russian Far East, Korean Peninsula and Japan), New Guinea and Australia. The African fauna was recently revised by Karisch (2013). In his revision, Karish offered a subdivision of the genus into 24 subgenera based on the differences in venation, configuration of androconial forewing lobes in males, pattern and genitalia structure.